Evaluating the effectiveness of multimedia courseware in imparting factual knowledge - Ibrahim, Azian; Krishnasamy, Hariharan N.; Abdullah, Syaharom (Universiti Utara Malaysia, 1996)
Integrating computers into the teaching and learning process as a means of simulating interest and generating creativity has become prevalent. However, there is still insufficient empirical evidence to suggest that computer assisted learning programs can motivate and facilitate learning. This paper attempts to investigate the effectiveness and the feasibility of employing an experimental multimedia course ware to supplement lectures at tertiary level. The course ware was designed to actively involve students in the learning process as well as to reduce the time allocated to impart factual knowledge in the classroom. Eight-one subjects who had registered for the Public Speaking course in the July 1996/1997 semester were randomly selected and divided into an experimental and two control groups. The experimental group went through the course ware without any classroom instruction of the content. One control group only went through classroom instruction and the subjects in the other control group read the material on their own. The performance of the experimental and control groups was compared using the pre and post test results. A questionnaire and a checklist were employed to elicit the experimental group's perception of and reaction to the course ware. The results of the study seem to suggest that the multimedia program is capable of helping subjects learn the material as well as allowing the learners better control of their learning. The restricted scope of the study, however does not permit a definitive conclusion. Whether this multimedia course ware could supplement or replace classroom teaching altogether will require future investigation.